Effect of water sorption on glass transition and microstructural variation of dextran & sugar mixtures. (15th August 2022) - Li, Wen; Yun, Liyuan; Zhao, Yunjiao; Zhi, Zijian; Muhindo, Esther Mwizerwa; Geng, Xiaoyuan; Liu, Rui; Wu, Tao; Sui, Wenjie; Zhang, Min
Abstract: Dextran is widely used as a model polysaccharide to study the interactions between polysaccharides and small molecule sugars. This study examined water sorption isotherms and glass transition temperatures ( T g ) of mixtures of dextran with trehalose, lactose and sucrose for understanding how different disaccharides affect dextran's processing adaptation and storage performance relevant to water sorption. At the same chemical composition, monolayer water ( m 0 ) was dextran & sucrose (dex&suc) > dextran & trehalose (dex&tre) > dextran & lactose (dex&lac). The higher ratios of dextran, the higher was the Guggenheim constant ( C ) value of the mixtures. The compatibility of dextran and disaccharides was dex&tre > dex&lac > dex&suc. Gordon–Taylor model showed dex&tre (2:1) best inhibited water plasticization. Furthermore, trehalose and lactose were more effective in preventing morphological changes of hydrous matrices in the mixtures. The crystallinities of samples at 43% relative humidity (RH) were slightly lower than that at 11% RH. Graphical abstract: Unlabelled Image